SISTEM INFORMASI PENGELOLAAN KIOS BERBASIS WEBSITE PADA POLI KIOS YOGYAKARTA - Linda Apriyanti; Abdurrahman; Windah Utari (LPPM STMIK Bandung, 2023)
Poli Kiosk is a kiosk rental for the people of Yogyakarta, but the shop ordering process records customerdata manually. This Poli Kiosk rental in the management of rental transactions still uses a manual system.From the existing problems, the author wants to apply information provision technology that can helpmanage Poli Kiosk rental transactions. In developing a Website-Based Kiosk Management InformationSystem at Poli Kiosk Yogyakarta, the author uses the waterfall development method, with the UML systemmodel and system development using the programming language (PHP5) and (HTML5) and the Laravelframework. Based on the results of the study, it was concluded that the information system created couldhelp manage rental transactions and provide information on Kiosk rentals.